1996
DOI: 10.1113/jphysiol.1996.sp021804
|View full text |Cite
|
Sign up to set email alerts
|

Activity and expression of Na(+)‐K(+)‐ATPase in human placental cytotrophoblast cells in culture.

Abstract: 1. To determine whether there is a change during differentiation, the activity and expression of Na(+)‐K(+)‐ATPase were studied in mononucleate cytotrophoblast cells (18 h culture) and syncytiotrophoblast‐like cells (66 h culture). A choriocarcinoma‐derived cell line (JAr) which, unlike the cytotrophoblast cells, divides in culture, was also studied for comparison. 2. Na(+)‐K(+)‐ATPase activity was assessed by measurement of ouabain‐sensitive 86Rb+ uptake. Na(+)‐K(+)‐ATPase expression was determined by (i) mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Alternatively, this anomaly might reflect efflux from a mixed population of cells. In the 66-h cytotrophoblast cell group, although the majority of cells are multinucleate and syncytiotrophoblast-like, some mononuclear cytotrophoblast cells are also present (7,8,18). In contrast, only multinucleate cells were selected for microfluorometry studies in the 66-h cytotrophoblast cell group.…”
Section: Rb Efflux Pathway In Cytotrophoblast Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, this anomaly might reflect efflux from a mixed population of cells. In the 66-h cytotrophoblast cell group, although the majority of cells are multinucleate and syncytiotrophoblast-like, some mononuclear cytotrophoblast cells are also present (7,8,18). In contrast, only multinucleate cells were selected for microfluorometry studies in the 66-h cytotrophoblast cell group.…”
Section: Rb Efflux Pathway In Cytotrophoblast Cellsmentioning
confidence: 99%
“…All cells were maintained at 37°C in a humidified incubator gassed with 5% CO 2-95% air for up to 3 days of culture. We have previously shown that during this time cytotrophoblast cells isolated from human term placenta undergo both morphological and biochemical differentiation to form multinuclear syncytiotrophoblast-like cells (7,18). Cells were studied at two time points in culture: after 18 h, when the majority of cells are mononuclear, and after 66 h, when the majority of cells are multinucleate syncytiotrophoblast-like cells.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Following isolation, cells were plated at a density of 5 million per 35 mm culture dish (Nunc) in 2 ml medium (Dulbecco's modified Eagle's medium (DMEM): F12 (diluted l:l), 10 % (v/v) fetal calf serum, 25 mM Hepes, pH 7.4, 0.12 YO (w/v) penicillin, 0.2 % (w/v) streptomycin and 0.6 % (w/v) glutamine) and kept in an incubator in 5 % CO and 95 % 0, at 37 "C for 66 h. The culture medium had a measured osmolality of 330 mosmol (kg H,O)-. All the experiments reported here were on cytotrophoblast cells kept in primary culture for 66 h. We have previously reported that after 66 h of primary culture cytotrophoblast cells aggregate and differentiate to form multinucleated cells which maximally secrete hCG Clarson et al 1996).…”
Section: Isolation Of Cytotrophoblast Cells and Cell Culturementioning
confidence: 99%